Pengaruh Pesan Kampanye Public Relations #SalingSilang Terhadap Sikap Followers Instagram Komunitas @lyfewithless - Rara Salsabila; Sofia Hasna (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
This research is motivated by the increasing amount of waste caused by high levels of public consumption, limited waste management facilities, and low environmental awareness. Lyfe With Less, an eco-friendly community, utilizes the function of Public Relations to deliver information and raise public awareness. This study aims to (1) identify the #SalingSilang campaign message conducted by Lyfe With Less, (2) examine the attitudes of Instagram followers of @lyfewithless toward the campaign, and (3) measure the influence of the #SalingSilang Public Relations campaign message on followers’ attitudes. The research applies the Campaign Message Design Theory, which includes message content, structure, and framing, as well as the Attitude Component Theory, which covers cognitive, affective, and conative aspects. A quantitative approach was used with a survey method by distributing questionnaires to 81 respondents selected randomly through probability sampling. The results show that the #SalingSilang campaign message received positive responses and had a significant and strong influence on followers’ attitudes. Within the Public Relations campaign message, the key message was found to be the most influential factor in the message content dimension, while in followers’ attitudes, the conative component showed the greatest change, particularly in reducing overconsumption and encouraging the optimal use of products.